Effectiveness of case method learning to optimise students' understanding of industrial mechanical machinery science - Putra, Rendy Dwi; Waskito; Arafat, Andril; García, Juan Luis Cabanillas; Ayasrah, Firas Tayseer Mohammad; Fortuna, Aprilla (Researcher and Lecturer Society, 2024)
Education has a central role in preparing individuals for the complexities of the modern world of work. Particularly in the context of education in Vocational High Schools, developing students' competencies in collaboration, creativity, and problem-solving is essential. This study explores the effectiveness of the case-based learning method in improving students' understanding of industrial mechanics. The study used a quasi-experiment design with control and experimental groups. The statistical analysis results showed that the case method was more effective in improving students' cognitive mastery than the conventional lecture method. Students who participated in case method learning showed significant improvement in the post-intervention test, demonstrating the superiority of this method in supporting a more effective learning process and preparing students for practical challenges in the field. In conclusion, the case method increases students' participation and interactivity in the learning process and deepens their understanding of technical concepts in industrial mechanics. This research provides a solid basis for implementing more effective and relevant learning methods in preparing vocational students for the increasingly complex needs of the world of work.